1972
DOI: 10.1159/000136283
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-Induced Redistribution of Cardiac Output in the Unanesthetized Monkey

Abstract: Regional blood flow measurements were made using the radioactive microsphere technique of Rudolph and Heymann [13] before Histamine and 3 times after the i.v. infusion of 2 mg/kg morphine in 9 unanesthetized monkeys restrained in horizontally tilted primate chairs. The dose was chosen after response curves established its minimal but consistent hypotensive effects. Although little systemic hemodynamic change was observed, the morphine evoked significant increases in blood flow to the heart, brain and bone, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…enkephalins elicit a pressure response in conscious, but a decrease in blood pressure in anaesthetized animals (see Lang et al, 1982). It has also been shown that morphine can cause an increase in cerebral blood flow in conscious animals (Miller et al, 1972;Koskinen & Bill, 1983) whereas under anaesthesia a decrease was seen (Takeshita et al, 1972;Buchweitz et al, 1984). The effects of various pharmacological agents on the single unit activity in the CNS is also affected by the consciousness of the animal (Trulson, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…enkephalins elicit a pressure response in conscious, but a decrease in blood pressure in anaesthetized animals (see Lang et al, 1982). It has also been shown that morphine can cause an increase in cerebral blood flow in conscious animals (Miller et al, 1972;Koskinen & Bill, 1983) whereas under anaesthesia a decrease was seen (Takeshita et al, 1972;Buchweitz et al, 1984). The effects of various pharmacological agents on the single unit activity in the CNS is also affected by the consciousness of the animal (Trulson, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin and aspirin-like nonsteroid antiinflammatory drugs (NSAID) still belong to the most widely distributed and most frequently used drugs [1]. However, even today, in spite of tremendeous research efforts their mode(s) of action in inflammation remains abscure or at least controversial [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its prevalent use, the effects of morphine on the heart and coronary vessels are poorly understood. Morphine is thought to have little effect on systemic hemodynamics (1,3,4), although both a transient decrease (5), or no change (1,3,4) in systemic vascular resistance as well as reduced (6)(7)(8) and enhanced (9) myocardial contractility have been observed. Despite its frequent use in patients with myocardial ischemia, little is known about the effects of morphine on the coronary vascular bed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its frequent use in patients with myocardial ischemia, little is known about the effects of morphine on the coronary vascular bed. Earlier studies concluded that it had little effect (8) or that it dilated the coronary bed (3,(10)(11)(12)(13). However, only one of these studies was conducted in the intact animal (3), and none measured coronary blood flow continuously or took into account changes in cardiac 1 Abbreviations used in this paper: dP/dt, rate of change of pressure; LV, left ventricular; MS, morphine sulfate.…”
Section: Introductionmentioning
confidence: 99%